Evaluation of Amplification Targets for the Specific Detection of Bordetella pertussis Using Real-Time Polymerase Chain Reaction. Issue 4 (2014) - Hasan, Mohammad Rubayet; Tan, Rusung; Al-Rawahi, Ghada N; Thomas, Eva; Tilley, Peter
Abstract : BACKGROUND: Bordetella pertussis infections continue to be a major public health challenge in Canada. Polymerase chain reaction (PCR) assays to detect B pertussis are typically based on the multicopy insertion sequence IS 481, which offers high sensitivity but lacks species specificity. METHODS: A novel B pertussis real-time PCR assay based on the porin gene was tested in parallel with several previously published assays that target genes such as IS 481, ptx -promoter, pertactin and a putative thialase. The assays were evaluated using a reference panel of common respiratory bacteria including different Bordetella species and 107 clinical nasopharyngeal specimens. Discrepant results were confirmed by sequencing the PCR products. RESULTS: Analytical sensitivity was highest for the assay targeting the IS 481 element; however, the assay lacked specificity for B pertussis in the reference panel and in the clinical samples. False-positive results were also observed with assays targeting the ptx -promoter and pertactin genes. A PCR assay based on the thialase gene was highly specific but failed to detect all reference strains of B pertussis . However, a novel assay targeting the porin gene demonstrated high specificity for B pertussis both in the reference panel and in clinical samples and, based on sequence-confirmed results, correctly predicted all B pertussis -positive cases in clinical samples. According to Probit regression analysis, the 95% detection limit of the new assay was 4 colony forming units/reaction. CONCLUSION: A novel porin assay for B pertussis demonstrated superior performance and may be useful for improved molecular detection of B pertussis in clinical specimens.